Pengaruh Rebranding dan Bauran Pemasaran Terhadap Kepuasan yang Berdampak pada Loyalitas Konsumen Mako - Lestari, Julianita; Meliana, Vina (STREAMING, 2023)
This study aims to determine the effect of rebranding and marketing mix on satisfaction which has an impact on Mako Cake and bakery consumer loyalty. This research uses nonprobability with purposive sampling technique and survey method with quantitative approach. The sample in this study were consumers who knew Mako Cake and bakery or who had bought Mako Cake and bakery products in Jabodetabek with a minimum age of 17 years and had a total of 170 samples. The results of this study indicate that rebranding affects satisfaction, marketing mix affects satisfaction, satisfaction affects consumer loyalty, rebranding and marketing mix together affect satisfaction.